Coming out strategies of lesbians and gays at work - Di Marco, D.; Arenas, A.; Munduate, L.; Hoel, H. (Revista de Psicologia Social, 2015)
In recent years there has been a great deal of social and legislative progress in the struggle against discrimination on grounds of sexual orientation. However, the coming out process in the workplace is still a crucial aspect in the lives of many lesbians and gays (LG). This study sets out to analyse the different strategies that Spanish LG adopt when revealing their sexual orientation at work by identifying the factors that facilitate or hinder this process. It also analyses the personal and organizational consequences of the strategies used in the coming out process. The study was carried out through in-depth interviews with 15 LG. Results show that the coming out strategies vary and are affected by different factors (e.g., characteristics of the colleagues, sector, etc.). Moreover, it confirmed that the coming out process (or its absence) can have consequences at different levels (e.g., relationships with colleagues, perception of organizational injustice, etc.).